Causes of hospitalization of elderly residents in a city of Paraná, an analysis of the last 5 years - Calíope Pilger; Maicon Henrique Lentsck; Gabriele de Vargas; Tatiane Baratieri (Universidade Federal de Santa Maria, 2011)
The research objective was to describe the profile of hospital morbidity and mortality of elderly residents in Guarapuava/PR, by sex and age in the last five years. Descriptive study with data collected in the database of the Hospital Information System in the period September to December 2010. The four diseases with higher prevalence of hospitalizations were the circulatory, respiratory, digestive and neoplasms, with a total of 7,069, 6,123, 1,931 and 1,676 admissions, respectively. Hospitalizations were higher for females, diseases of the circulatory, respiratory, already in the digestive system diseases and cancer, the prevalence was higher in males. With these data there is a need for new policies, review in hospital care, to offer to this age population with an effective and quality service